A tale of SARS-CoV-2 genomic surveillance in Mali: Variants introductions and transmission dynamics - Noumou Yakhouba Keita; Harris Onywera; Mahamadou Abdou; Zeinaba Dicko; Fankélé Mamadou Diarra; Ousmane Kamena; Amidou Diarra; Klèma Marcel Koné; Alhadji Alassane Dicko; Demba Koita; Tinimba Sountoura; Oumar Samaké; et al. (PLoS ONE, 2026)
Despite the global scale of SARS-CoV-2 genomic surveillance, data from West Africa are limited. In Mali 33,197 confirmed cases and 743 deaths (case fatality ratio: 2.23%) were recorded between March 2020 and August 2025. This study aimed to provide the first comprehensive genomic reconstruction of SARS-CoV-2 variant introductions, transmission pathways, and evolutionary trends in Mali from 2020 to 2023. A total of 548 Malian sequences were used for lineages assignment and variant tracking. For the reconstruction of transmission dynamic a high quality subset of 305 Malian sequences (passing 90% coverage) was analysed alongside 142 closely related global genomes (from 20 countries) identified using the UShER. Time-resolved phylogenetic reconstruction, ancestral trait inference, and molecular clock analyses were performed with TreeTime v0.11.4 to infer variant introductions, local transmission, and substitution rates. Genomic and epidemiological data revealed five distinct epidemic waves driven by the temporal succession of global variants, from 19A/20A lineages in early 2020 to dominant XBB sublineages in 2023. Multiple independent viral introductions were traced primarily to Europe and North America, followed by sustained local and intercontinental transmission, including reciprocal exchanges with neighbouring African countries. The substitution rate was estimated to be 1.56 x 10−3 substitutions per site per year, consistent with global evolutionary trends. Entropy analysis revealed high genetic variability within the spike gene, particularly in the receptor-binding domain. These findings underscore the persistent global connectivity and local evolutionary pressure shaping the trajectory of the pandemic in Mali. These call for the need for sustained genomic surveillance capacity to inform epidemic preparedness and response.